Interactions between four common plant-derived phenolic acids and pectin, and its effect on antioxidant capacity - González-Aguilar, Gustavo A. (2018)
Phenolic acids (PAs) are molecules of vegetable origin with high antioxidant capacity (AOXC) attributed to their hydroxyl groups. Vegetable cells store PAs within vacuoles, and when disrupted through mastication or food processing, PAs can interact with other molecules like fibers, which alters their AOXC. Mango (Mangifera indica L.) cv Ataulfo contains PAs and fiber, particularly pectin. Previous reports indicate that PAs interact between themselves and affect each other’s AOXC. The present work analyzed the interactions between the main PAs from mango cv Ataulfo and pectin, and how pectin affects their AOXC. We used UV–Vis spectrophotometry, fluorescence spectrophotometry and AOXC assays to study how pectin influences gallic, protocatechuic, chlorogenic and vanillic acid, individually, and in combinations of two, three and four PAs. Results showed that gallic acid was the most affected by the presence of pectin, which was related to its number and position of hydroxyl groups. The effect of pectin was not as obvious when three or four PAs were combined, suggesting that PAs preferentially interact among themselves, likely through hydrogen bonds. Pectin exerted mostly synergistic effects on AOXC values when added to one, two and four combined PAs; antagonistic effects were recorded when pectin was added to three combined PAs. The effect of pectin on AOXC was more noticeable when analyzed by the ORAC assay, and less when analyzed by the DPPH assay. Basic knowledge of the interactions between PAs and pectin is of great importance, since they are normally consumed alongside each other.